Inflammatory/Immune Adverse Events in Chronic Myeloid Leukemia Patients During Treatment With Bosutinib - E. Agostani; E. Tassistro; L. Antolini; C. Gambacorti‐Passerini (Cancer Medicine, 2025)
ABSTRACT Background Bosutinib, a tyrosine kinase inhibitor (TKI), is effective in treating chronic myeloid leukemia (CML) patients resistant or intolerant to previous TKIs. Unlike other TKIs, bosutinib's lack of inhibition of c‐KIT and PDGFR may contribute to its unique tolerability profile. Similar to dasatinib, it targets Bcr/Abl and SRC kinases, particularly Lyn, raising safety concerns. In fact, the susceptibility of Lyn −/− mice to autoimmune disorders and the deregulation of Lyn‐dependent pathways in patients with lupus were previously shown. Aims This study aimed to assess the time‐adjusted rate (TAR) of inflammatory/immune‐related adverse events in bosutinib‐treated patients. Methods We analyzed clinical data from 60 patients with a minimum follow‐up of three months. We used the CTCAE dictionary to identify immune‐related adverse events (irAEs). Results Patients had a median treatment duration of 47.9 months (IQR: 38.4–121.8), totaling 592.7 person‐months. Among 33 patients (55% of the sample), we detected 94 irAEs (2.3% of total adverse events), including giant cell arteritis, psoriasis, erythema nodosum, articular pain, pleural and pericardial effusion, and three cases of recurrent sterile pneumonia. The estimated TAR of the first irAEs was 14.7 (95% CI: 10.4–20.7) events per 100 person‐years; considering repeated irAEs, the TAR was 28.4 (95% CI: 23.2–34.8) events per 100 person‐years. The median time to the first irAE was 14.8 months (IQR: 7.1–42). These rates are higher than those observed in imatinib‐treated patients. Conclusions Our findings support the clinical impression of a high incidence of irAEs in bosutinib‐treated patients and may lead to an enhanced understanding of bosutinib's safety profile and mechanism of action.